Skills of a successful software engineer - Doglio, Fernando (Manning Publications, 2022)
Skills of a Successful Software Engineer is a best practices guide for succeeding on a software development team. The book reveals how to optimize both your code and your career, from achieving a good work-life balance to writing the kind of bug-free code delivered by pros. You'll master essential skills that you might not have learned as a solo coder, including meaningful code commenting, unit testing, and using refactoring to speed up feature delivery. Timeless advice on acing interviews and setting yourself up for leadership will help you throughout your career. Crack open this one-of-a-kind guide, and you'll soon be working in the professional manner that software managers expect.